Adherence to healthy lifestyle improved clinical outcomes in coronary artery disease patients after coronary intervention. Issue 6 (2nd June 2021) - Yang, Ya-Ling; Leu, Hsin-Bang; Yin, Wei-Hsian; Tseng, Wei-Kung; Wu, Yen-Wen; Lin, Tsung-Hsien; Yeh, Hung-I; Chang, Kuan-Cheng; Wang, Ji-Hung; Wu, Chau-Chung; Chen, Jaw-Wen
Abstract : Background: Lifestyle modification is suggested for patients with coronary artery disease (CAD), but the impact of adherence to a healthy lifestyle remains undetermined. The aim of this study is to investigate the association of adherence to a healthy lifestyle with future outcomes and biochemical markers in CAD patients. Methods: The Biosignature CAD study examined 716 CAD patients who underwent a percutaneous coronary intervention (PCI). Information was collected on whether these patients adhered to a healthier lifestyle after PCI, including healthy diet, not smoking, and exercise. The clinical outcomes included major cardiovascular events and unplanned revascularization procedures, hospitalization for refractory or unstable angina, and other causes Results: The average follow-up period was 26.8 ± 8.1 months, during which 175 (24.4%) patients experienced at least one event. The combination of healthy lifestyle factors was associated with lower risk, and the maximum risk reduction reached 50% (hazard ratio: 0.50, 95% confidence interval: 0.25-0.99). As the number of healthy lifestyle factors increased, there were decreases in inflammatory markers, C-reactive protein, waist circumference, low-density lipoprotein cholesterol, and the ratio of total cholesterol to high-density lipoprotein (HDL) cholesterol ( p < 0.05). The benefits of modifiable healthy lifestyle factors were especially observed in the younger population, males, patients with HDL <40 mg/dL, those with reduced left ventricular ejection fraction, and those receiving statin therapy. Conclusion: Adherence to a healthy lifestyle is independently associated with a lower risk of future adverse events in CAD patients and plays an important role in secondary prevention in the era of interventional cardiology.